Surprising Conformers of the Biologically Important A·T DNA Base Pairs: QM/QTAIM Proofs - Brovarets', Ol'ha O.; Tsiupa, Kostiantyn S.; Hovorun, Dmytro M. (Frontiers in Chemistry, 2018)
For the first time novel high-energy conformers – А·Т(wWC) (5.36), А·Т(wrWC) (5.97), А·Т(wН) (5.78) and А·Т(wrН) (∆G=5.82 kcal∙mol-1) were revealed for each of the four biologically important А·Т(WC) DNA base pairs – Watson-Crick А·Т(WC), reverse Watson-Crick А·Т(rWC), Hoogsteen А·Т(Н) and reverse Hoogsteen А·Т(rН) at the MP2/aug-cc-pVDZ//B3LYP/6-311++G(d,p) level of quantum-mechanical theory in the continuum with ε=4 under normal conditions. Each of these conformers possesses substantially non-planar wobble (w) structure and is stabilized by the participation of the two anti-parallel N6H/N6H´…O4/O2 and N3H…N6 H-bonds, involving the pyramidalized amino group of the A DNA base as an acceptor and a donor of the H-bonding. The transition states – TSА·Т(WC)↔А·Т(wWC), TSА·Т(rWC)↔А·Т(wrWC), TSА·Т(Н)↔А·Т(wН) and TSА·Т(rН)↔А·Т(wrН), controlling the dipole-active transformations of the conformers from the main plane-symmetric state into the high-energy, significantly non-planar state and vice versa, were localized. They also possess wobble structures similarly to the high-energy conformers and are stabilized by the participation of the N6H/N6H´…O4/O2 and N3H…N6 H-bonds. Discovered conformers of the А·Т DNA base pairs are dynamically stable short-lived structures (lifetime τ = (1.4-3.9) ps). Their possible biological significance and future perspectives have been briefly discussed.